Keragaman Plasma Nutfah Pisang (Musa sp) di Pulau Bangka Berdasarkan Karakter Morfologi - Lesta Lesta; Eries Dyah Mustikarini; Gigih Ibnu Prayoga (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2018)
Banana (Musa sp) is a plant that has good nutrion, mineral, vitamin A, B complex, vitamin C, and vitamin B6. Germplasm diversity of local banana in Bangka has never been identified. Research about germplasm diversity of banana in Bangka Island need to maintain germplasm of Bangka local banana. This research was conducted in Bangka Island. Characterization of banana fruit germplasm includes on qualitative and quantitative traits. Analysis of morphological relationship of banana fruit germplasm used UPGMA. Exploration result obtained 22 germplasms of Bangka local banana. The result of relationship analysis showed four clusters at 0,40 (40%) coefficient. Cluster one consists of Udang germplasm. Cluster two consists of Jernang and Rotan germplasm. Cluster three consists of Wei, Kapal and Abu germplasm. Cluster four consists of Madu Manis, Madu Keling, Gambur, Jambi, 40 Hari, Bawang, Geda, Tematu, Serindit, Masak Ijau, Rejang, Madu Pulau, Kecit Lantai, Susu, Gede and Lilin germplasm. Bangka local banana have wide variability in almost morphological character observed.